Speciation analysis of elements accumulated in Cystoderma carcharias from clean and smelter-polluted sites - Borovička, Jan; Braeuer, Simone; Sácký, Jan; Kameník, Jan; Goessler, Walter; Trubač, Jakub; Strnad, Ladislav; Rohovec, Jan; Leonhardt, Tereza; Kotrba, Pavel (The Science of the total environment, 2019)
Collections of Cystoderma carcharias sporocarps were sampled from clean and smelter-polluted sites and analyzed for Ag, As, Cd, Cu, Pb, Se, and Zn contents. Concentrations of all elements were significantly higher in samples from the smelter-polluted area. Except for As and Pb, all elements were effectively accumulated in the sporocarps at both clean and polluted sites. With the highest concentration of 604 mg Cd kg-1, C. carcharias can be considered as Cd hyperaccumulator. As revealed by HPLC-ICPQQQMS analysis, the As species in sporocarps from clean and polluted areas involved besides the major arsenobetaine a variety of known and unknown arsenicals; the occurrence of dimethylarsinoylacetate and trimethylarsoniopropionate is reported for the first time for gilled fungi (Agaricales). Size-exclusion chromatography of C. carcharias extracts supported by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and RP-HPLC data indicated that detoxification of intracellular Cd and Cu may largely rely on metallothioneins (MT) or MT-like peptides, not phytochelatins.
Keywords: Metals; Copper; Agaricales; Environmental Monitoring; Soil Pollutants; látky znečišťující půdu; Hyperaccumulation; Zinc; kovy; polokovy; Arsenic species; Selenium; Cadmium; monitorování životního prostředí; Metalloids; arsen; Czech Republic; Arsenic; Metallurgy; Česká republika; hutnictví